Реализация инновационной стратегии государства при создании и производстве фармацевтической продукции на региональном рынке - Федоренко, Ирина Анатольевна (Луганський національний університет імені Тараса Шевченка, 2010)
Исследованы научные перспективы и предложены возможные направления формирования и реализации инновационной стратегии государства при создании и производстве фармацевтической продукции на региональном рынке.

Research investigated the perspectives and suggested possible areas of development and innovation strategy of the state in creating and producing pharmaceutical products in the regional market.
Realization of innovation strategy of the state during creation and manufacturing of pharmaceutical production on the regional market
Keywords: фармацевтическая отрасль; фармацевтический рынок; стратегические приоритеты развития; pharmaceutical branch; pharmaceutical market; basic challenges of development